2022
DOI: 10.3389/fmars.2022.859428
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid-Lowering Effect of Dietary Taurine in Orange-Spotted Groupers (Epinephelus coioides) Involves Both Bile Acids and Lipid Metabolism

Abstract: An 8-week feeding trial was conducted to investigate how dietary taurine supplementation attenuates the lipid deposition induced by dietary high lipid in juvenile orange-spotted grouper (Epinephelus coioides). Three isonitrogenous (47% crude protein) semipurified diets were formulated to contain two levels of lipid and termed as 10% lipid diet, 15% lipid diet, and 15% lipid with 1% taurine (namely, diet 10L, diet 15L, and diet 15L + T, respectively). Groupers fed diet 15L + T showed higher weight gain and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…However, the underlying mechanism involved in the regulation of lipid metabolism still remains unclear. Recent studies have shown that dietary taurine supplementation in 15% fat feed could reduce lipid accumulation through reducing the contents of triglyceride molecules containing 18:2n–6 at the sn – 2 and sn – 3 positions [ 25 ] and through accelerating lipid absorption of taurine−conjugated bile acids and fatty acid β-oxidation, and inhibiting lipogenesis [ 26 ]. However, determining how dietary taurine modulates lipid metabolism of fish at the transcriptional level has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism involved in the regulation of lipid metabolism still remains unclear. Recent studies have shown that dietary taurine supplementation in 15% fat feed could reduce lipid accumulation through reducing the contents of triglyceride molecules containing 18:2n–6 at the sn – 2 and sn – 3 positions [ 25 ] and through accelerating lipid absorption of taurine−conjugated bile acids and fatty acid β-oxidation, and inhibiting lipogenesis [ 26 ]. However, determining how dietary taurine modulates lipid metabolism of fish at the transcriptional level has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%